A combined control method of supply harmonic current and source harmonic voltage for series hybrid active power filter - Thuyen, Chau Minh; Nguyen, Hoai Thuong; Thao, Phan Thi Bich (International Journal of Electrical and Computer Engineering (IJECE), 2024)
The series hybrid active power filter (SHAPF) is known as a very effective harmonic filtering model in power systems. Typically, SHAPF is controlled by a control method based either on the harmonic voltage of the load or on the supply harmonic current. However, the above two methods have the disadvantage of requiring the control coefficient much be large enough, which easily causes system instability. Therefore, this paper presents a new control method for SHAPF. It is a combined control method of the supply harmonic current and the source harmonic voltage. The advantage of the proposed method is the ability to reduce the total harmonic distortion of the supply current and voltage applied to the load with a control coefficient that is not too large. A fuzzy-proportional integral controller is designed for the proposed control method to reduce the compensation error in steady state under variable load conditions. Mathematical models and simulation results have demonstrated the effectiveness of the proposed method in reducing the total harmonic distortion of the supply current, voltage applied to the load and minimize the compensation error at steady state.